Импульсное обжатие цилиндрической оболочки - Лотоус, В. В.; Наумова, Е. А.; Драгобецкий, В. В. (НТУ "ХПИ", 2014)
В статье приведено описание технологий основанных на действии кумулятивных зарядов взрывчатого вещества на обрабатываемый материал. Рассмотрены вопросы использования энергии взрыва для распада и синтеза химических элементов в кумулятивной струе. Приведено качественное описание процесса обжатия цилиндрической оболочки кумулятивным зарядом взрывчатого вещества. Образующиеся при обжатии оболочки гофры становятся источниками системы кумулятивных струй. Исследования позволили разработать новые технологии взрывного упрочнения и легирования и метод физического моделирования обжатия вязких материалов

The description of technologies of the cumulative charges, based on action, of explosive Description of technologies based on the effect of cumulative charges of an explosive substance on the treated material is given. The issues of using the explosive energy for disintegration and synthesis of chemical elements in the cumulative jet are considered. A qualitative description of the reduction process of a cylindrical envshell by the cumulative charge of an explosive substance is given. Corrugations formed at reduction of a shell become the sources of a system of cumulative jets. The researches have allowed to develop new technologies of explosive hardening and alloying and a method of physical modeling the reduction of viscous materials
Impulse crimp of cylindric shell
Keywords: взрывные технологии; взрывчатые вещества; гофрообразование; кумуляция; плазма; химические элементы; explosive technologies; cumulation; plasma; chemical elements; explosive substances; corrugation forming